The Effect of emotional intelligence and work culture on performance through employee commitment - Faradiba Pababari; Nur Naninsih; Muhajir Muhajir (Vifada Management and Digital Business, 2025)
This study employs a quantitative approach, as the data collected consists of numerical data or other information that can be analysed using statistical techniques. The study was conducted at a local government office, namely the Regional Secretariat of West Sulawesi Province, with a sample of 107 employees. The primary method used in this study was the distribution of questionnaires. The data analysis techniques employed in this study were Path Analysis and the Sobel Test. The results of the study indicate that: 1) Emotional intelligence has a positive and significant effect on employee commitment at the Regional Secretariat of West Sulawesi Province. 2) Work culture has a positive and significant effect on employee commitment at the Regional Secretariat of West Sulawesi Province. 3) Emotional intelligence has a positive and significant effect on employee performance at the Regional Secretariat of West Sulawesi Province. 4) Work culture has a positive and significant effect on employee performance at the Regional Secretariat of West Sulawesi Province. 5) Job commitment has a positive and significant effect on employee performance at the Regional Secretariat of West Sulawesi Province. 6) Emotional intelligence has a positive and significant effect on performance via employees’ work commitment at the Regional Secretariat of West Sulawesi Province. 7) Work culture has a positive and significant effect on performance via employees’ work commitment at the Regional Secretariat of West Sulawesi Province.